What Are Karelians Made of, RuNet? - Oivo, Teemu (Journal on Ethnopolitics and Minority Issues in Europe, 2022)
The social construction of the concepts of Karelian people, culture, and land develops in temporal flux. In the 2010s, the expansion of internet usage empowered previously unheard voices engaging these concepts in Russia. In this article, Russian-language internet discussions are used to find out how the state of Karelianness was negotiated in Russian-language internet (RuNet) discussions in the 2010s. My research distinguishes how manifestations of (sub)national identifications were dialectically approved and disapproved in accordance with nationalism discourses that I codify as civic, regionalist, and ethnic. The discussions show how the territory of the Republic of Karelia defines the boundaries within which manifestations of Karelianness are considered. Moreover, they depict the critique and rejection of issues such as Karelian culture, language, and descent due to their perceived juxtaposition against Russianness. Peer reviewed